2021
DOI: 10.3892/mmr.2021.12303
|View full text |Cite
|
Sign up to set email alerts
|

miR‑34a increases inflammation and oxidative stress levels in patients with necrotizing enterocolitis by downregulating SIRT1 expression

Abstract: The mir-34a/SirT1 signaling axis is an important signaling axis in tumors and diseases. notably, low SirT1 expression in the intestinal tissues of patients with necrotizing enterocolitis (nec) has been reported. However, whether mir-34a/SirT1 signaling as a target to protect the intestines during the nec process is unclear and remains to be elucidated. Blood samples were collected from 30 patients with nec, and an nec rat model was used. The mir-34a and SirT1 gene and protein expression levels were assayed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The prolonged exposure of saturated fatty acids to MIN6 β-cells and pancreatic islets increased the expression of miR-34a ( Lovis et al, 2008 ). Furthermore, miR-34a leads to endothelial dysfunction and vascular senescence in diabetes ( Li et al, 2016 ; Carracedo et al, 2019 ; Thounaojam and Bartoli, 2019 ), increasing the overall risk of oxidative stress and inflammation with or without diabetes ( Li et al, 2016 ; Cheleschi et al, 2019 ; Xiong et al, 2019 ; Zimta et al, 2019 ; Li et al, 2021 ; Mahjabeen et al, 2021 ; Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged exposure of saturated fatty acids to MIN6 β-cells and pancreatic islets increased the expression of miR-34a ( Lovis et al, 2008 ). Furthermore, miR-34a leads to endothelial dysfunction and vascular senescence in diabetes ( Li et al, 2016 ; Carracedo et al, 2019 ; Thounaojam and Bartoli, 2019 ), increasing the overall risk of oxidative stress and inflammation with or without diabetes ( Li et al, 2016 ; Cheleschi et al, 2019 ; Xiong et al, 2019 ; Zimta et al, 2019 ; Li et al, 2021 ; Mahjabeen et al, 2021 ; Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al . found that miR-34a was notably upregulated in NEC, which could promote the production of inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-8) and anti-inflammatory cytokines IL-10 by downregulating sirtuin1 (SIRT1) expression ( 39 ). Xia et al .…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al . found that intestinal villi injury can be ameliorated by miR-34a inhibitors and SIRT1 activators ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations